ChemInform Abstract: New Phosphine Oxide Aziridinyl Phosphonates as Chiral Lewis Bases for the Abramov‐Type Phosphonylation of Aldehydes. Issue 45 (14th October 2013) - Dogan, Oezdemir; Isci, Muhammet; Aygun, Muhittin
Abstract Newly synthesized chiral aziridine bisphosphonates are examined for the phosphonylation of aldehydes.